Mapping the Potential of Field Laboratories on Mount Galunggung for Learning the Concept of Plantae Biology - Hidayah, Nurul; Hernawati, Diana; Putra, Rinaldi Rizal (Bioeduca : Journal of Biology Education, 2024)
Biology education emphasizes the importance of teacher facilitation both inside and outside the classroom. Field laboratory experiences are crucial for deepening conceptual understanding and complementing classroom learning. This research aims to describe the types of mosses and ferns in the Gunung Galunggung area and to map its potential as a field laboratory. The research method used is an exploratory survey through direct observation, interviews, literature studies, field observations, and documentation studies. Data analysis was conducted qualitatively and descriptively using the Milles and Hubberman approach, classifying Gunung Galunggung into 3 stations with 9 zones. The research results show that Gunung Galunggung has 10 genera of mosses from 8 families and 16 genera of ferns from 13 families, indicating significant potential as a field laboratory. This study is expected to serve as a reference for educators and biology students for independent practicum activities in the Gunung Galunggung area.